Comparing Problem-based Learning and Experiential Learning on Civil Servant Training Program - Sediyani, Linda; Budisantoso, Heri Triluqman (Indonesian Journal of Curriculum and Educational Technology Studies, 2019)
Problem-based learning and experiential learning are well-known learning approaches and often referred as powerful on facilitating learning practices, but which one is the most effective on facilitating civil servant training program? This article illustrates a one-shot case study in which focus on one civil servant training program only without comparing it to other programs. The training program was conducted by human resource development agency, Central Java Province, in March 2018. By employing quantitative research approach, this research found that the result of the training program indicated: there are no significant differences between problem-based learning and experiential learning approaches. In this case, the learning result from experiential learning approach is slightly above problem-based learning approach’s result. Abstrak Pembelajaran berbasis masalah dan berbasis pengalaman merupakan pendekatan pembelajaran yang sudah banyak dikenal dan sering disebut mampu memfasilitasi praktik pembelajaran secara optimal, namun mana di antaranya keduanya yang paling efektif dalam memfasilitasi program pelatihan PNS? Artikel ini menggambarkan one-shot case study yang fokus hanya pada satu program pelatihan PNS tanpa membandingkannya dengan program lain. Program pelatihan ini dilakukan oleh Badan Pengembangan Sumber Daya Manusia (BPSDM), Provinsi Jawa Tengah, pada Maret 2018. Dengan menggunakan pendekatan penelitian kuantitatif dapat dilihat bahwa hasil program pelatihan menunjukkan tidak terdapat perbedaan yang signifikan antara pembelajaran berbasis masalah dan pembelajaran berbasis pengalaman. Dalam hal ini, hasil pembelajaran dari pendekatan berbasis pengalaman sedikit di atas hasil pembelajaran yang menggunakan pendekatan pembelajaran berbasis masalah.